Dental Management of Patients Receiving Oral Bisphosphonate Therapy - Rattanaudom, Rachadaporn (Journal of Health Science of Thailand, 2017)
A clinical dental guideline for patients taking oral bisphosphonates especially dental treatment which involves medullary bone and periosteum such as dental extraction, impaction removal, osteoplasty and periodontal surgery which may increase the risk of developing osteonecrosis of the jaw,dentists should take dental consideration and special precaution before treatment such as complete medical history, current systemic diseases, currently receiving medication, history of cancer treatment and age of patient for evaluation and proper treatment planning to reduce the risk of developing osteonecrosis of the jaw.